2009
DOI: 10.1103/physrevb.79.024304
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary optical transmission induced by excitation of a magnetic plasmon propagation mode in a diatomic chain of slit-hole resonators

Abstract: In this paper, we will propose that magnetic resonance nanostructures in a metal surface could be used to realize extraordinary optical transmission (EOT). Toward this goal, we designed and fabricated a one-dimensional diatomic chain of slit-hole resonator (SHR). Due to the strong exchange current interaction, a type of magnetic plasmon (MP) propagation mode with a broad frequency bandwidth was established in this system. Apparent EOT peaks induced by the MP mode were observed in our measured spectra at infrar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In this figure, we can see that the extraordinary optical transmission (EOT) peak is induced by MPW, changing from 230 to 200 THz, by tuning the incidence angle θ from 0 0 to 40 0 . In this measurement, EOT can be obtained for the normal incidence wave ( 0 =0 θ ), which did not occur in our previous work [28] .In the following model, we show that this is caused by the electric resonance in the slits. …”
Section: Numerical Model and Experimental Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this figure, we can see that the extraordinary optical transmission (EOT) peak is induced by MPW, changing from 230 to 200 THz, by tuning the incidence angle θ from 0 0 to 40 0 . In this measurement, EOT can be obtained for the normal incidence wave ( 0 =0 θ ), which did not occur in our previous work [28] .In the following model, we show that this is caused by the electric resonance in the slits. …”
Section: Numerical Model and Experimental Resultsmentioning
confidence: 96%
“…Compared with the near-field magnetic and electric coupling, this interaction is much stronger and can lead to coherent magnetic plasmon waves with broad dispersive frequency bands and a slow group velocity of light. In our experimental work [28], a diatomic chain of SHRs was devised with a unit cell, including two SHRs with equal-length slits and different-sized holes. The extraordinary transmission peaks induced by the excitation of the coherent MPWs in such a system can be directly observed in our experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with usual one-layer grating like the crystal with one atom in the primitive cell, the two-layer grating is the crystal with two atoms in the primitive cell. Similar to a diatomic chain of slit-hole resonators [15], the dispersion relations of twolayer grating is divided into optical mode and acoustic mode while only acoustic dispersion branch for one-layer grating. The upper optical branch easily intersects with the incident light line while the lower acoustic branch below the light line.…”
Section: Calculated Results and Discussionmentioning
confidence: 99%
“…Along with the rapid advancement in metamaterials research, magnetic plasmon polaritons (MPs) have been recognized as a mechanism for highfrequency magnetic response in some artificial nanostructures [13,14]. Recently, magnetic resonance has been employed to achieve EOT in a diatomic chain of slit-hole resonators [15] and metallic deep gratings [16] at infrared frequencies. Usually magnetic plasmon resonance occurs in nanostructures much smaller in size than the optical wavelength [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on periodic gratings have revealed that localized magnetic polaritons (MPs), which are responsible for extraordinary transmission in metamaterials (Liu et al, 2006(Liu et al, , 2009, can also occur in periodic gratings to significantly alter the thermal radiative properties of the structure (Lee et al, 2008c). Figure 13 illustrates the effect of MP for a deep grating structure ).…”
Section: Manipulation Of Radiative Propertiesmentioning
confidence: 99%